The transmissivity of one-dimensional photonic crystals comprising three phases nanocomposite layer for optical switching purposes. (27th July 2021) - Mohamed, Aliaa G; ElSayed, Hussein A; Mehaney, Ahmed; Aly, Arafa H; Sabra, Walied
Abstract: In the present work, we have demonstrated the optical properties of a one-dimensional photonic crystal structure in which silicon (Si) and a nanocomposite material represent the constituent layers. The nanocomposite (NC) layer is designed from nanoparticles (NPs) of silver (Ag) and Indium Tin Oxide (ITO) in a host medium of air. The optical properties of the proposed design have been theoretically investigated using the well-known transfer matrix method (TMM), Maxwell-Garnett model and generalized Rayleigh mixing formula as well. The numerical results deduce that the effective permittivity of the nanocomposite material is strongly affected by the type and filling fraction of the NPs. Moreover, the effect of other related parameters such as the thickness of NC layer, filling fractions of NPs, permittivity of the background dielectric medium, the radius of Ag NPs and carrier density of ITO NPs on the optical characteristics of our design is also considered. We believe that the proposed structure may be useful as optical filters, reflectors, and optical switches.